(3cJGH Ydhe GdMOjKs - (3EHQGgje Hf eMeO Hf YHO Gddg Hf GdgGOj GdhRjQj,J (B914 (3g` s ((3eMeO Hf EHQGgje s)
(3ChdgG (B:s
(3GdMeO ddg GdeJNU HGdbOe hENQGL GdYGde Yf eMV GdYOe hHYO aEf CaVd GdYdhe eYQaI cJGH Gddg hSfg QShdI s
(3BNQgG (B:s
(3hEPG EJabhG Ydi CUd GdMOjK hGNJdahG ai SjGbg RjGOg Ch fbUGf , Ch JQc HYV GSe GdQGhi PcQJg HCMSf SjGb hGdLedI hHGddg CSJeO GdJhajb hGdEYGfg Ydi Sdhc gPg GdWQjbI GfJgi eG PcQg QMeg Gddg ai gPg GdebOeI GdePchQI s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM hHYV GdcdeGJ HGdNW GdSejc HBNQgG SeGYGJ hJedcGJs
(3HChdgG bUjOI ejejI gOjI ef QLd gfOis
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs